MODERATION IN DSN-MUI FATWAS: Achieving Justice and Balance in the Sharia Economic System - Fakhruddin, Fakhruddin; Hidayat, Hakmi; Firdaus, Dwi Hidayatul (Jurisdictie: Jurnal Hukum dan Syariah, 2024)
Religious practices in Indonesia are heavily influenced by a fiqh-oriented perspective, emphasizing legalistic approaches to various issues. This drives the government to seek legitimacy from religious scholars, particularly through the Indonesian Ulema Council (MUI) and its Fatwa Commission, along with the National Sharia Council (DSN), which play central roles in issuing fatwas on Sharia economics. This study explores DSN-MUI’s methodology in fatwa issuance and its integration of moderation values, focusing on justice and balance. Utilizing textual analysis and data triangulation for validation, the research employs descriptive and evaluative methods. The findings indicate that DSN-MUI employs methodologies such as nash qath’i (definitive textual evidence), qauli (scholarly opinions), and manhaji (methodological reasoning), along with solutions like al-Taysir al-Manhaji (methodological facilitation) and Tafriq al-Halal ‘an al-Haram (differentiation of lawful and unlawful). While fatwas emphasize moderation, practical implementation requires reinforcement through regulations, education, and adaptation to contemporary contexts. This study enriches academic discourse by emphasizing the integration of moderation values in building an inclusive Islamic economy and highlights leveraging technology to enhance fatwa relevance and effectiveness in addressing modern economic challenges.Praktik keagamaan di Indonesia sangat dipengaruhi oleh perspektif berbasis fiqh yang menekankan pendekatan legalistik terhadap berbagai isu. Hal ini mendorong pemerintah untuk mencari legitimasi dari ulama, khususnya melalui Majelis Ulama Indonesia (MUI) dan Komisi Fatwa-nya, serta Dewan Syariah Nasional (DSN) yang berperan penting dalam penerbitan fatwa ekonomi syariah. Penelitian ini mengeksplorasi metodologi yang digunakan oleh DSN-MUI dalam penerbitan fatwa dan integrasi nilai moderasi, dengan fokus pada keadilan dan keseimbangan. Menggunakan analisis tekstual dan triangulasi data untuk validasi, penelitian ini menerapkan metode deskriptif dan evaluatif. Hasilnya menunjukkan bahwa DSN-MUI menggunakan metodologi seperti nash qath’i (dalil tekstual definitif), qauli (pendapat ulama), dan manhaji (penalaran metodologis), serta solusi seperti al-Taysir al-Manhaji (kemudahan metodologis) dan Tafriq al-Halal ‘an al-Haram (pembedaan antara yang halal dan haram). Meskipun fatwa-fatwa tersebut menekankan moderasi, implementasi praktisnya masih memerlukan penguatan melalui regulasi, pendidikan, dan penyesuaian dengan konteks kontemporer. Penelitian ini memperkaya wacana akademik dengan menekankan integrasi nilai moderasi dalam membangun ekonomi Islam yang inklusif, serta pentingnya memanfaatkan teknologi untuk meningkatkan relevansi dan efektivitas fatwa dalam menghadapi tantangan ekonomi modern.